From inner to dyadic connection: the role of mindfulness in mother–infant interaction during the first year of life - Passaquindici, Ilenia; Pastore, Massimiliano; Nardozza, Odette; Lionetti, Francesca; D’Urso, Giulio; Palumbo, Riccardo; Fasolo, Mirco; Spinelli, Maria (Frontiers in Behavioral Neuroscience, 2024)
Introduction Mother–infant attunement is fundamental to supporting infant socio-emotional development. Based on the assumption that we connect better with others if we are aware of and connected with our own experience, mindfulness could affect the maternal ability to attune to the infant. However, little is known about this topic in the first year of life. Study 1 aimed to investigate the role of maternal dispositional mindfulness and mindful parenting in mother–infant physiological and behavioral attunement at 3 months of age. Study 2 aimed to explore the effect of a mindfulness-based intervention not specific to parenting experience on mother–infant behavioral and physiological attunement and on maternal wellbeing at 9 months of age. Methods In Study 1, mother–infant (n = 67) behavioral and physiological attunement (i.e., co-regulation and RSA) were collected simultaneously each 20 s during face-to-face interaction. Mothers completed questionnaires about their dispositional mindfulness and mindful parenting. In Study 2, mother–infant dyads were randomly divided into a control (n = 20) and an intervention group (n = 29). The intervention group attended a 5-week mindfulness-based intervention. At T1 and T2, the same procedure described in Study 1 was applied and mothers reported about their wellbeing. Results Results showed that maternal mindfulness was associated with high physiological and behavioral attunement at 3 months and with more positive maternal behaviors and less stress at 9 months. Analysis evidenced a slight improvement in the intervention group in maternal dispositional mindfulness and a reduction in parenting stress at T2. Discussion Findings from both studies suggested that maternal mindfulness could represent a protective factor that could support mothers in fostering better dyadic interactions with their infants. The implementation of mindfulness-based interventions for mothers could have preventive and clinical implications.